The Correlation of Statistical Image and Partial Discharge Pulse Count of LDPE-NR Composite - Aulia Aulia; Zulkarnain Abdul Malek; Yanuar Zulardiansyah Arief; Eka Putra Waldi (Universitas Ahmad Dahlan, 2017)
High voltage insulation must be designed in such a way that it is very resistant to ageing including that from partial discharge (PD). Many studies were previously carried out on composites based on low density polyethylene (LDPE). However, the use of natural rubber (NR) and nanosilica (SiO2) in the LDPE-NR based composites is relatively new. Furthermore, the PD resistant performance of the composites is yet to be extensively researched. This work aims to analyze the correlation between PD pulse count and its related image to interpreting the effect of PD signals. The results show there is a strong correlation between PD pulse count and the statistical image. The results indicate that the surface image statistical analysis can be used as a tool to justify the total of the PD pulse count on the surface for different samples of composite.